An efficient medium to intercalate metals into graphite: LiCl-KCl molten salts. (April 2019) - Fauchard, Mélissa; Cahen, Sébastien; Bolmont, Mickaël; Medjahdi, Ghouti; Lagrange, Philippe; Hérold, Claire
Abstract: A new synthesis method using molten salts has been achieved allowing the intercalation of metals (e.g europium) into graphite. This method consists in dissolving various metals in a LiCl-KCl medium intended to be intercalated. In this work, many reactions are carried out by dissolving metals of first and second columns of the periodic table (Li, Na, K, Mg, Ca, Sr, Ba) in the molten salts before performing intercalation reactions for periods ranging from few minutes to several days and for temperatures included between 400 and 450 °C. The obtained compounds are then characterized by X-ray diffraction. Three different behaviors have been observed. With alkali metals, the obtained GIC is systematically LiC6 GIC. Magnesium leads to a sample of pure graphite remaining pristine. In case of alkaline earth metals, calcium, strontium and barium, the intercalation of the metal is systematically observed. The method presented in this paper reports for the first time the synthesis of a bulk SrC6 GIC. Finally, the intercalation mechanism using this medium has been deduced from these results and thanks to a study performed by ex situ X-ray diffraction in the case of the formation of the EuC6 GIC. Graphical abstract: Image 1063